Insecticidal and Repellent Activity of Several Plant-Derived Essential Oils Against Aedes aegypti - Castillo, Ruth M; Stashenko, Elena; Duque, Jonny E (Journal of the American Mosquito Control Association, 2017)
We examined the pupicidal, adulticidal, repellent, and oviposition-deterrent activities of essential oils (EOs) from Lippia alba, L. origanoides, Eucalyptus citriodora, Cymbopogon citratus, Cymbopogon flexuosus, Citrus sinensis, Cananga odorata, Swinglea glutinosa, and Tagetes lucida plants against Aedes aegypti under laboratory conditions. Pupicidal and adulticidal activities were assessed at exploratory concentrations of 250, 310, and 390 parts per million (ppm); and 30, 300, and 1,000 ppm, respectively. The greatest pupicidal activity was exhibited at 390 ppm with a 24-h exposure by L. origanoides, and 390 ppm with a 48-h exposure by Citrus sinensis. Lippia origanoides killed all adult mosquitoes at 300 ppm after 120 min of exposure. Only L. origanoides and E. citriodora EOs, applied at 1,000 ppm to human skin, produced the greatest repellency (100%) to host-seeking Ae. aegypti after 2 min of exposure; the repellency decreased between 12% and 10% after 15 min. Complete oviposition deterrence by gravid Ae. aegypti was observed for E. citriodora EOs at 200 ppm with an oviposition activity index of −1.00. These results confirm that the EOs assessed in this study have insecticidal, repellent, and oviposition-deterrent activities against the dengue vector, Ae. aegypti.